Effect of CD26/dipeptidyl peptidase IV on Jurkat sensitivity to G(2)/M arrest induced by topoisomerase II inhibitors - Aytac, U (Nature Publishing Group, 2003)
CD26/dipeptidyl peptidase IV (DPPIV) is a surface antigen with multiple functions, including a role in T-cell activation and the development of certain human cancers. We previously demonstrated that CD26/DPPIV enhanced sensitivity of Jurkat cells to doxorubicin. We now show that expression of CD26/DPPIV enhanced sensitivity of CD26 Jurkat transfectants to G(2)–M arrest mediated by the antineoplastic agent etoposide. The increased sensitivity to etoposide-induced G(2)–M arrest was associated with disruption of cell cycle-related events, including hyperphosphorylation of p34(cdc2) kinase, change in cdc25C expression and phosphorylation, and alteration in cyclin B1 expression. CD26/DPPIV-associated enhancement of doxorubicin and etoposide-induced G(2)–M arrest was also observed in serum-free media, suggesting an effect of CD26 on cell-derived processes rather than serum-derived factors. Importantly, our work elucidated a potential mechanism for the enhanced susceptibility of CD26-expressing Jurkat cells to the topoisomerase II inhibitors by demonstrating that CD26/DPPIV surface expression was associated with increased topoisomerase II α levels and enhanced enzyme activity. Besides being the first to show a functional association between the multifaceted molecule CD26 and the key cellular protein topoisomerase II α, our studies provide additional evidence of a potential role for CD26 in the treatment of selected malignancies.